EFFECT OF CORN DDGS ON EXTRUSION PROCESSING PARAMETERS AND PHYSICAL QUALITY OF EXTRUDED CATFISH FEED - Ilić, Petar (Journal on Processing and Energy in Agriculture, 2024)
Four iso-nitrogenous European catfish (Silurus glanis) diets (protein content approximately 400 g/kg) with the inclusion of 0, 100, 200 and 300 g/kg of corn DDGS were formulated and processed by twin-screw extruder. The aim was to assess the influence that DDGS has on extrusion processing and physical quality properties of sinking feed. All ingredients of the diets were finely ground at the hammer mill, mixed and steam conditioned to a temperature of 95 °C and moisture content of approximately 250 g/kg prior to the extrusion. The conditioned mixtures were processed by twin-screw extruder in order to produce sinking pellets. The DDGS inclusion in catfish diets decreased specific mechanical energy during extrusion, which significantly (p
Keywords: DDGS; catfish; extrusion; energy consumption; physical quality